Benznidazole treatment safety: the Médecins Sans Frontières experience in a large cohort of Bolivian patients with Chagas’ disease - Silva, Gilberto Marcelo Sperandio da (2017)
This study was supported by the international medical humanitarian organization Me´decins Sans Frontie`res (MSF) and the Evandro Chagas National Institute of Infectious Diseases (INI) of the Oswaldo Cruz Foundation (Fiocruz), Rio de Janeiro, Brazil, Programa Estrate gico de Apoio a Pesquisa em Saude (Papes VII)/Conselho Nacional de Desenvolvimento Cientıfico e Tecnologico (CNPq), Brazil (grant 401878/ 2015–5 to G. S. d. S.).